Rifaximin Reduces Markers of Inflammation and Bacterial 16S rRNA in Zambian Adults with Hepatosplenic Schistosomiasis: A Randomized Control Trial - Sinkala, Edford (Am J Trop Med Hyg, 2018)
Cirrhosis is the dominant cause of portal hypertension globally but may be overshadowed by hepatosplenic schistosomiasis (HSS) in the tropics. In Zambia, schistosomiasis seroprevalence can reach 88% in endemic areas. Bacterial translocation (BT) drives portal hypertension in cirrhosis contributing to mortality but remains unexplored in HSS. Rifaximin, a non-absorbable antibiotic may reduce BT. We aimed to explore the influence of rifaximin on BT, inflammation, and fibrosis in HSS. In this phase II open-label trial (ISRCTN67590499), 186 patients with HSS in Zambia were evaluated and 85 were randomized to standard care with or without rifaximin for 42 days. Changes in markers of inflammation, BT, and fibrosis were the primary outcomes. BT was measured using plasma 16S rRNA, lipopolysaccharide-binding protein, and lipopolysaccharide, whereas hyaluronan was used to measure fibrosis. Tumor necrosis factor receptor 1 (TNFR1) and soluble cluster of differentiation 14 (sCD14) assessed inflammation. 16S rRNA reduced from baseline (median 146 copies/µL, interquartile range [IQR] 9, 537) to day 42 in the rifaximin group (median 63 copies/µL, IQR 12, 196), P < 0.01. The rise in sCD14 was lower (P < 0.01) in the rifaximin group (median rise 122 ng/mL, IQR-184, 783) than in the non-rifaximin group (median rise 832 ng/mL, IQR 530, 967). TNFR1 decreased (P < 0.01) in the rifaximin group (median -39 ng/mL IQR-306, 563) but increased in the non-rifaximin group (median 166 ng/mL, IQR 3, 337). Other markers remained unaffected. Rifaximin led to a reduction of inflammatory markers and bacterial 16S rRNA which may implicate BT in the inflammation in HSS.